2013
DOI: 10.1128/jb.02061-12
|View full text |Cite
|
Sign up to set email alerts
|

The Stringent Response Controls Catalases in Pseudomonas aeruginosa and Is Required for Hydrogen Peroxide and Antibiotic Tolerance

Abstract: e Pseudomonas aeruginosa, a human opportunistic pathogen, possesses a number of antioxidant defense enzymes under the control of multiple regulatory systems. We recently reported that inactivation of the P. aeruginosa stringent response (SR), a starvation stress response controlled by the alarmone (p)ppGpp, caused impaired antioxidant defenses and antibiotic tolerance. Since catalases are key antioxidant enzymes in P. aeruginosa, we compared the levels of H 2 O 2 susceptibility and catalase activity in P. aeru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 79 publications
7
125
0
4
Order By: Relevance
“…Other mechanisms such as the development of swarming colonies, the stringent response, i.e. response to nutrient limitation, and the formation of multiresistant subpopulation of persistent cells contribute to the multidrug-resistant phenotype [21][22][23] . Furthermore, P. aeruginosa is versatile in the development or acquisition of new mechanisms of resistance to antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mechanisms such as the development of swarming colonies, the stringent response, i.e. response to nutrient limitation, and the formation of multiresistant subpopulation of persistent cells contribute to the multidrug-resistant phenotype [21][22][23] . Furthermore, P. aeruginosa is versatile in the development or acquisition of new mechanisms of resistance to antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding stringent response, for P. aeruginosa and E. coli growing in biofilms it was found that stringent response was necessary for maintaining the low levels of reactive oxygen species (ROS) (ref. 12,13 ) which are associated with apoptosis-like death 14 . Furthermore, Aizenman and coworkers described that overexpression of ppGpp induced mazEF death pathway through the stable toxin MazF which is able to exert its deleterious effects and cause cell death 15 .…”
Section: Introductionmentioning
confidence: 99%
“…A reduced expression of rpoS in the presence of AgCNTs in both strains may suggest a decreased ability for survival under stress imposed by AgCNTs, whereas an increased expression in the presence of gentamicin may suggest the opposite. It is known that the general oxidative stress regulator and alternative sigma factor, RpoS 35 regulates the expression of more than 35 genes, many of which are involved in the general stress response. RpoS also plays a role as an intermediary regulator of catalase activity and hydrogen peroxide (H 2 O 2 ) tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in P. aeruginosa, the stringent response is required for optimal catalase activity and mediates H 2 O 2 tolerance during both planktonic and biofilm growth. Upon amino acid starvation, induction of the stringent response upregulates catalase activity (119). The demonstration of a link between the stringent response and oxidative stress defense is interesting, as ROS have been proposed to explain antibiotic-induced bacterial cell death (120)(121)(122).…”
Section: Persisters Play a Central Role In Biofilm Recalcitrance Towamentioning
confidence: 99%